2019
DOI: 10.1371/journal.pone.0221481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vascular endothelial growth factor levels in tears and serum among diabetic patients

Abstract: Objective Detection of vascular endothelial growth factor (VEGF) levels in ocular tissue may perhaps provide insight into the role of VEGF in the pathogenesis and progression of diabetic retinopathy (DR). The aim of this study was to evaluate the levels of VEGF in tears and serum amongst type 2 diabetes mellitus (DM) patients. Methods A comparative cross-sectional study was conducted between August 2016 and May 2018 involving type 2 DM patients with no DR, non-prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
2
32
2
Order By: Relevance
“…Some clinical and biochemical biomarkers such glycaemia, HbA1c, blood pressure, blood lipid concentrations, and ocular coherence tomography (OCT) are routinely used as biomarkers in the monitoring of patients with diabetes. Among pro-inflammatory and angiogenic factors, we can single out VEGF which has enabled the development of anti-VEGF treatment ( 14 , 17 , 26 , 36 , 37 , 39 , 54 ). Many other molecules are used in basic science studies investigating the pathogenesis of DR or as surrogate end-points in preclinical studies that explore new therapy options ( 6 , 47 , 48 ).…”
Section: The Role Of Biomarkers In Diabetic Retinopathy Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Some clinical and biochemical biomarkers such glycaemia, HbA1c, blood pressure, blood lipid concentrations, and ocular coherence tomography (OCT) are routinely used as biomarkers in the monitoring of patients with diabetes. Among pro-inflammatory and angiogenic factors, we can single out VEGF which has enabled the development of anti-VEGF treatment ( 14 , 17 , 26 , 36 , 37 , 39 , 54 ). Many other molecules are used in basic science studies investigating the pathogenesis of DR or as surrogate end-points in preclinical studies that explore new therapy options ( 6 , 47 , 48 ).…”
Section: The Role Of Biomarkers In Diabetic Retinopathy Managementmentioning
confidence: 99%
“…Diabetic retinopathy biomarkers which more accurately reflect the pathology of the posterior segment of the eye, are those determined from the AH and vitreous ( 47 , 48 ). However, these are difficult to obtain and entail invasive procedures to collect the sample ( 21 - 23 , 26 - 28 , 31 - 34 , 36 - 39 , 47 , 48 , 51 - 54 , 56 , 57 ).…”
Section: Collection and Analysis Of Ocular Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all tested uveal melanomas expressed VEGF mRNA [189]. In another study, and always using healthy eye samples as a control, high levels of VEGF were also found in vitreous and anterior chamber fluids of affected eyes [192]. In several studies, including the study by Missotten et al, higher VEGF concentrations have also been reported in the aqueous humour of the affected eyes, possibly justifying the larger basal diameter and the height of the uveal melanoma.…”
Section: Uveal Melanoma Angiogenesis and Anti-angiogenic Therapymentioning
confidence: 91%
“…Therefore, increased serum levels of VEGF are an important tool for risk evaluation in diabetic retinopathy. Its serum and vitreous levels correlate with severity of disease [16,17]. Inflammation is a key component in diabetes-associated retinal damages.…”
mentioning
confidence: 99%